Bitdefender: Mid-Year Threat Landscape Report 2019. Issue 12 (December 2019) - Unknown
Abstract : One of the key messages of this research from Bitdefender is that ransomware is thriving – and that's in spite of one of the most virulent forms having largely disappeared earlier this year. In the first six months, ransomware infections detected by the company's telemetry increased 74.23% compared to the same period in 2018.